Lithium primary battery
By using specific materials and additives in the nonaqueous electrolyte in the positive electrode and negative electrode of the lithium primary battery, the problem of capacity reduction in the negative electrode deterioration in the lithium primary battery is solved, and the effect of high capacity and low capacity degradation rate is achieved.
Patent Information
- Application Number
- CN202380059601.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-24
- Filing Date
- 2023-08-23
- Publication Date
- 2025-03-28
AI Technical Summary
The deterioration of the negative electrode in the lithium primary battery leads to a decrease in the battery capacity.
The positive electrode is used to include a selected group consisting of manganese dioxide and graphite fluorinated, and the negative electrode contains lithium alloy. The lithium alloy contains aluminum, magnesium and trace amounts of sodium and calcium. The total content of aluminum and magnesium is between 0.02% and 10%, and the total content of sodium and calcium is below 0.02%, and a cyclic imide compound, a phthalate compound and isocyanate compound are added as additives to the nonaqueous electrolyte solution.
It effectively suppresses the reduction of lithium primary battery capacity, improves the initial and long-term storage capacity of the battery, and significantly reduces the capacity degradation rate after storage.
Smart Images

Figure CN119731792A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to lithium primary batteries. Background Art
[0002] Lithium primary batteries are used as power sources for many electronic devices because of their high energy density and low self-discharge. The positive electrode of a lithium primary battery uses manganese dioxide or the like. The negative electrode of a lithium primary battery uses, for example, sheet-shaped (foil-shaped) metal lithium or a lithium alloy.
[0003] Patent document 1 proposes a lithium negative electrode. In a lithium-organic electrolyte battery in which a lithium salt is dissolved in an electrolyte and a separator is placed opposite to the negative electrode, lithium formed by initially stacking a covering layer of an aluminum-magnesium alloy relative to the surface of a lithium body adjacent to the separator is used as a negative electrode, and an aluminum-magnesium-lithium ternary alloy is formed by diffusion, thereby increasing the surface area of the negative electrode and enhancing the pulse performance of the battery.
[0004] Patent document 2 proposes an electrochemical cell, characterized in that it includes a cathode assembly, wherein the cathode assembly is formed by a metal cathode current collector having two main surfaces and a cathode covering layer arranged on at least one of the two main surfaces, the covering layer contains iron disulfide and also has a metal lithium anode alloyed with aluminum, and the input ratio of the anode to the cathode is less than 1.0.
[0005] Patent document 3 proposes a lithium primary battery comprising: a positive electrode using iron disulfide as a positive electrode active material, a negative electrode using a lithium alloy as a negative electrode active material, an electrode group formed by winding the positive electrode and the negative electrode with a separator between them, and a non-aqueous electrolyte, wherein the lithium alloy contains 0.02 to 0.2 mol % of at least one of magnesium and tin.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 58-209862
[0009] Patent Document 2: Japanese Patent Application No. 2005-529467
[0010] Patent Document 3: International Publication No. 2012 / 066709 Pamphlet Summary of the invention
[0011] Problem that the invention aims to solve
[0012] In lithium primary batteries, the battery capacity may decrease due to deterioration of the negative electrode.
[0013] Solutions for solving problems
[0014] One aspect of the present disclosure relates to a lithium primary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte, wherein the positive electrode comprises at least one selected from the group consisting of manganese dioxide and graphite fluoride, and the negative electrode comprises a lithium alloy, wherein the lithium alloy comprises aluminum, magnesium, and at least one selected from the group consisting of sodium and calcium, wherein the total content of the aluminum and the magnesium in the lithium alloy is 0.02 mass % or more and 10 mass % or less, and the total content of the sodium and the calcium in the lithium alloy is 0.02 mass % or less.
[0015] Effects of the Invention
[0016] According to the present disclosure, it is possible to suppress a decrease in the capacity of a lithium primary battery.
[0017] Although the novel features of the present invention are described in the attached claims, both the technical solution and the content of the present invention can be further fully understood through the following detailed description with reference to the accompanying drawings in combination with other objects and features of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a front view showing a part of a lithium primary battery according to an embodiment of the present disclosure as a cross section. DETAILED DESCRIPTION
[0019] Hereinafter, the embodiments of the present disclosure will be described with examples, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values and materials are sometimes exemplified, but other numerical values and materials may also be applied as long as the effects of the present disclosure can be obtained. In this specification, the so-called "numerical value A to numerical value B" includes numerical value A and numerical value B, and can be read alternatively as "above numerical value A and below numerical value B". In the following description, when lower limits and upper limits are exemplified for numerical values of specific physical properties, conditions, etc., any one of the exemplified lower limits can be arbitrarily combined with any one of the exemplified upper limits as long as the lower limit does not exceed the upper limit. When multiple materials are exemplified, one can be selected from them and used alone, or two or more can be used in combination.
[0020] In addition, the present disclosure includes a combination of matters recorded in two or more claims arbitrarily selected from the plurality of claims recorded in the attached claims. That is, as long as no technical contradiction occurs, matters recorded in two or more claims arbitrarily selected from the plurality of claims recorded in the attached claims may be combined.
[0021] A lithium primary battery of one embodiment of the present disclosure comprises a positive electrode, a negative electrode and a non-aqueous electrolyte. The positive electrode comprises at least one selected from the group consisting of manganese dioxide and graphite fluoride. The negative electrode comprises a lithium alloy, and the lithium alloy comprises aluminum (Al), magnesium (Mg) and at least one selected from the group consisting of sodium (Na) and calcium (Ca). The total content of Al and Mg in the lithium alloy is greater than 0.02% by mass and less than 10% by mass. The total content of Na and Ca in the lithium alloy is less than 0.02% by mass. In the lithium alloy, Al, Mg and at least one selected from the group consisting of Na and Ca are mixed.
[0022] When the lithium alloy contains Al, the side reaction caused by the contact between the negative electrode and the non-aqueous electrolyte can be suppressed, and the capacity reduction caused by the side reaction can be suppressed. On the other hand, Al is easily segregated in the lithium alloy. Due to the segregation of Al, the consumption of Li on the negative electrode surface during discharge becomes uneven, and the local defect or fracture of the negative electrode at the end of discharge sometimes reduces the capacity.
[0023] In contrast, by including Mg together with Al in the lithium alloy, the segregation of Al in the lithium alloy can be suppressed, the suppressing effect of Al on the above-mentioned side reaction can be stably obtained in the entire negative electrode, and Li can be uniformly consumed on the negative electrode surface. The deterioration of the negative electrode caused by the segregation of Al in the negative electrode can be suppressed, and the proportion of Li that contributes to the discharge reaction can be increased even at the end of discharge, which can suppress the reduction of capacity.
[0024] Furthermore, by including at least one selected from the group consisting of Na and Ca in a lithium alloy containing Al and Mg in an amount of less than 0.02% by mass, the dispersibility of Mg can be improved, the inhibitory effect of Mg on the above-mentioned Al segregation can be significantly obtained, and the reduction in capacity can be significantly suppressed. Therefore, a high capacity can be obtained in any case of initial and long-term storage, and the capacity degradation rate after storage can be greatly reduced. When the total content of Na and Ca in the lithium alloy is less than 0.02% by mass, a trace amount of Na and / or Ca is dissolved in the lithium alloy and is easily dispersed evenly, which can stably and effectively contribute to improving the dispersibility of Mg.
[0025] However, when the total content of Al and Mg in the lithium alloy is less than 0.02% by mass, the effect brought by Al and Mg becomes insufficient, and the capacity is easily reduced. In addition, when the total content of Al and Mg in the lithium alloy is greater than 10% by mass and / or the total content of Na and Ca in the lithium alloy is greater than 0.02% by mass, the amount of Li occupied in the negative electrode is reduced, and the absolute amount of Li is reduced, so sometimes the capacity is reduced. When the total content of Na and Ca in the lithium alloy is greater than 0.02% by mass, Na and / or Ca are difficult to be dissolved in the lithium alloy, the dispersibility of Mg is reduced, and sometimes the capacity is reduced.
[0026] (negative electrode)
[0027] The lithium alloy used in the negative electrode is, for example, in the form of foil (sheet). From the viewpoint of high capacity, the content of Li in the lithium alloy may be, for example, 90% by mass or more, or 95% by mass or more. The lithium alloy contains Al and Mg and contains at least one selected from the group consisting of Na and Ca.
[0028] The total content of Al and Mg in the lithium alloy is 0.02 mass % or more and 10 mass % or less, can be 0.05 mass % or more (or 0.1 mass % or more) and 8 mass % or less, or can be 0.1 mass % or more (or 0.2 mass % or more) and 5 mass % or less.
[0029] The Mg content (or Al content) in the lithium alloy can be 0.02% by mass or more, 0.05% by mass or more, or 0.1% by mass or more (or 0.2% by mass or more). In addition, the Mg content (or Al content) in the lithium alloy can be 9.5% by mass or less, 7% by mass or less, 5% by mass or less, or 2% by mass or less. The molar ratio of Mg to Al: Mg / Al can be, for example, 0.01 or more (or 0.02 or more) and 100 or less, or 0.05 or more and 20 or less.
[0030] The total content of Na and Ca in the lithium alloy is 0.02 mass % or less, may be 0.0005 mass % or more and 0.019 mass % or less, or may be 0.001 mass % or more and 0.018 mass % or less.
[0031] The Na content (or Ca content) in the lithium alloy can be 0.0001 mass % or more, 0.0005 mass % or more, or 0.0025 mass % or more. In addition, the Na content (or Ca content) in the lithium alloy can be 0.015 mass % or less, 0.012 mass % or less, or 0.010 mass % or less.
[0032] The lithium alloy may include other metal elements other than Li, Al, Mg, Na and Ca. As other metal elements, Sn, Ni, Pb, In, K, Fe, Si, etc. can be listed. From the viewpoint of ensuring the discharge capacity and stabilizing the internal resistance, the overall content of the metal elements other than lithium contained in the lithium alloy is preferably 0.05 mass % or more and 15 mass % or less (or 10 mass % or less).
[0033] The content of each element in the lithium alloy is determined by inductively coupled plasma (ICP) emission spectrometry or atomic absorption spectrometry (AAS).
[0034] (Additives for non-aqueous electrolytes)
[0035] The non-aqueous electrolyte preferably contains at least one additive selected from the group consisting of a cyclic imide compound, a phthalate compound and an isocyanate compound. In the case where the non-aqueous electrolyte contains the above-mentioned additive, a composite coating containing Al and Mg from the lithium alloy and components from the additive can be formed on the surface of the lithium alloy (negative electrode) containing Al and Mg. The chemical stability of the coating is excellent, and the coating contains Al and Mg from the lithium alloy, so the wettability of the negative electrode to the non-aqueous electrolyte can be improved, and the resistance of the negative electrode can be reduced. Through the coating, it is easier to evenly consume Li on the surface of the negative electrode. In addition, by further containing at least one of Na and Ca in the lithium alloy, Mg is more evenly dispersed, and the uniformity in the entire negative electrode is further improved. Therefore, it is easy to stably form the above-mentioned coating. As a result, it is easy to further suppress the reduction in capacity.
[0036] The content of the additive in the non-aqueous electrolyte is, for example, more than 0.01% by mass and less than 5% by mass. It should be noted that the content of the additive in the non-aqueous electrolyte is the mass ratio (percentage) of the additive relative to the entire non-aqueous electrolyte. For example, just after the battery is manufactured (or when the non-aqueous electrolyte is prepared), the content of the additive in the non-aqueous electrolyte is expected to be within the above range. In contrast, in a battery that has just been manufactured for a certain period of time, a portion of the additive is consumed during the formation of the coating, and the content of the additive in the non-aqueous electrolyte may also be a value less than the above range. In this case, even if the content of the additive in the non-aqueous electrolyte is a small amount (e.g., a value close to the detection limit), the above-mentioned effect brought about by the additive can be confirmed. The same is true for the content of various compounds such as cyclic imide compounds described later.
[0037] (Cyclic imide compound)
[0038] As the cyclic imide compound, for example, a cyclic diacylamine compound can be cited. The cyclic imide compound may have a diacylamine ring (hereinafter, also referred to as an imide ring). Other rings (hereinafter, also referred to as the second ring) may also be condensed in the imide ring. The cyclic imide compound may be contained in the non-aqueous electrolyte in the form of an imide or in the form of an anion or a salt. In the case where the cyclic imide compound is contained in the non-aqueous electrolyte in the form of an imide, it may be contained in the form of a free NH group or in the form of a tertiary amine.
[0039] Examples of the second ring include an aromatic ring, a saturated or unsaturated aliphatic ring, etc. The second ring may also contain at least one heteroatom. Examples of the heteroatom include an oxygen atom, a sulfur atom, and a nitrogen atom.
[0040] Examples of cyclic imide compounds include aliphatic dicarboxylic acid imide compounds and cyclic imide compounds having a second ring. Examples of aliphatic dicarboxylic acid imide compounds include succinimide. Examples of cyclic imide compounds having a second ring include imide compounds of aromatic or alicyclic dicarboxylic acids. Examples of aromatic dicarboxylic acids or alicyclic dicarboxylic acids include substances having carboxyl groups on two adjacent atoms constituting the ring. Examples of cyclic imide compounds having a second ring include phthalimide and hydrogenated products of phthalimide. Examples of hydrogenated products of phthalimide include cyclohex-3-ene-1,2-dicarboximide and cyclohexane-1,2-dicarboximide.
[0041] The imide ring may also be an N-substituted imide ring having a substituent on the nitrogen atom of the imide. Examples of such substituents include hydroxyl groups, alkyl groups, alkoxy groups, and halogen atoms. Examples of alkyl groups include C1 to C4 alkyl groups, which may be methyl groups, ethyl groups, and the like. Examples of alkoxy groups include C1 to C4 alkoxy groups, which may be methoxy groups, ethoxy groups, and the like. Examples of halogen atoms include chlorine atoms and fluorine atoms, and the like.
[0042] The cyclic imide compound is preferably selected from at least one of the group consisting of phthalimide and N-substituted phthalimide. As a substituent on the nitrogen atom of the N-substituted phthalimide, it can be selected from the substituents exemplified for the N-substituted imide ring. N-substituted phthalimide, for example, preferably includes at least one selected from the group consisting of N-hydroxyphthalimide, N-(2-hydroxyethyl)phthalimide, N-(cyclohexylthio)phthalimide and N-(phenylthio)phthalimide. Phthalimide and / or N-substituted phthalimide can account for more than 50% by mass of the cyclic imide compound, and further can account for more than 70% by mass or more than 90% by mass.
[0043] The non-aqueous electrolyte may contain one cyclic imide compound, or may contain two or more. The content of the cyclic imide compound in the non-aqueous electrolyte may be 1% by mass or less, may be 0.001% by mass or more and 1% by mass or less, or may be 0.001% by mass or more and 0.8% by mass or less.
[0044] (Phthalate Compounds)
[0045] Phthalic acid ester compounds include phthalic acid esters and derivatives thereof. The derivatives may have a substituent bonded to an aromatic ring derived from phthalic acid. Examples of such substituents include hydroxyl groups, alkyl groups, alkoxy groups, and halogen atoms. Examples of alkyl groups include C1 to C4 alkyl groups, which may be methyl groups, ethyl groups, and the like. Examples of alkoxy groups include C1 to C4 alkoxy groups, which may be methoxy groups, ethoxy groups, and the like. Examples of halogen atoms include chlorine atoms and fluorine atoms, and the like.
[0046] The phthalate compound may be a phthalate monoester compound, but from the viewpoint that the resulting coating is easy to protect the surface of the Li alloy, a phthalate diester compound is desirable. As the alcohol constituting the ester with phthalic acid (or its derivative), a saturated or unsaturated aliphatic alcohol of C1 to C20 (preferably C1 to C6) is desirable.
[0047] Specific examples of phthalic acid diester compounds include dimethyl phthalate, diethyl phthalate, diallyl phthalate, dibutyl phthalate, diisobutyl phthalate, bis(2-ethylhexyl)phthalate, etc. These may be used alone or in combination of two or more. The phthalic acid diester compound may account for 50% by mass or more of the phthalate ester compound, and may also account for 70% by mass or more or 90% by mass or more.
[0048] The non-aqueous electrolyte solution may contain one phthalate compound or two or more phthalate compounds. The content of the phthalate compound in the non-aqueous electrolyte solution may be 1% by mass or less, or may be 0.1% by mass or more and 1% by mass or less.
[0049] (Isocyanate compound)
[0050] The isocyanate compound has, for example, at least one isocyanate group and a C1-C20 aliphatic hydrocarbon group or a C6-C20 aromatic hydrocarbon group. The aliphatic hydrocarbon group and the aromatic hydrocarbon group constituting the isocyanate compound may have a substituent. The substituent may be a group that can exist stably, for example, a halogen atom or a nitrile group. The aliphatic group may be an alicyclic aliphatic group, or a linear or branched aliphatic group. The aromatic hydrocarbon group is a hydrocarbon group having one or more aromatic rings, or a group in which an aromatic ring is connected to an aliphatic group.
[0051] The isocyanate compound may be a monoisocyanate compound having one isocyanate group, but is preferably a diisocyanate compound having two isocyanate groups. It is believed that the diisocyanate compound generates a composite film having higher chemical stability than the monoisocyanate compound, and generates a composite film having lower resistance than the triisocyanate. In addition, even if the diisocyanate compound is in a small amount, the ability to form a composite film is high, and the stability in the battery is excellent.
[0052] Specific examples of diisocyanate compounds include OCN-C n H 2n -NCO (n is an integer of 1 to 10.) represented by a compound (for example, hexamethylene diisocyanate), a compound having an alicyclic diyl group (for example, 1,3-bis(isocyanatomethyl)cyclohexane, dicyclohexylmethane-4,4'-diisocyanate, bicyclo[2.2.1]heptane-2,5-diylbis(methylisocyanate), bicyclo[2.2.1]heptane-2,6-diylbis(methylisocyanate), isophorone diisocyanate), 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, hexyl isocyanate, etc. Among these, at least one selected from the group consisting of hexamethylene diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane and isophorone diisocyanate is preferred. These may account for 50% by mass or more of the isocyanate compound, and may further account for 70% by mass or more or 90% by mass or more.
[0053] When a diisocyanate compound is added to a non-aqueous electrolyte, the diisocyanate compounds react with each other in the battery (in the non-aqueous electrolyte) to form an isocyanurate body, a urea body, or a biuret body. Therefore, when the battery is decomposed and the non-aqueous electrolyte is analyzed, an isocyanurate body, a urea body, or a biuret body derived from the diisocyanate compound is sometimes detected.
[0054] The non-aqueous electrolyte may contain one isocyanate compound, or may contain two or more. The content of the isocyanate compound in the non-aqueous electrolyte may be 3% by mass or less, 0.01% by mass or more and 2% by mass or less, or 0.01% by mass or more and 1.5% by mass or less.
[0055] The non-aqueous electrolyte solution (additive) can be analyzed by, for example, liquid chromatography mass spectrometry (LC / MS) and gas chromatography mass spectrometry (GC / MS), nuclear magnetic resonance analysis (NMR), infrared absorption spectroscopy (IR), mass spectrometry (MS), and ultraviolet spectroscopy (UV).
[0056] Hereinafter, the lithium primary battery of the present disclosure will be described in more detail.
[0057] [Lithium primary battery]
[0058] (positive electrode)
[0059] The positive electrode contains at least one selected from the group consisting of manganese dioxide and graphite fluoride as a positive electrode active material. When the positive electrode is used, it is beneficial to improve the initial capacity and the capacity after long-term storage. As manganese dioxide, electrolytic manganese dioxide can be suitably used. The positive electrode containing manganese dioxide shows a higher voltage, which is beneficial in improving the discharge characteristics (pulse discharge characteristics). Manganese dioxide can be a mixed crystal state containing a variety of crystal states. The positive electrode may contain manganese oxides other than manganese dioxide. As manganese oxides other than manganese dioxide, MnO, Mn 3 O 4 , Mn 2 O 3 , Mn 2 O 7 The main component of the manganese oxide contained in the positive electrode is preferably manganese dioxide. The so-called main component here means that the proportion of manganese dioxide in the manganese oxide is 50% by mass or more. The proportion of manganese dioxide in the manganese oxide can be 70% by mass or more, or 90% by mass or more.
[0060] If iron disulfide is used as the positive electrode active material for the negative electrode containing the above lithium alloy, the capacity may decrease after long-term storage. It is speculated that the following effects are caused: Fe and S are dissolved from the positive electrode containing iron disulfide, and side reactions occur with Al and Mg in the negative electrode (lithium alloy), and a film containing Fe and S is formed on the surface of the negative electrode along with the side reaction, and the negative electrode reaction is non-uniform due to the film.
[0061] The positive electrode may include a positive electrode mixture containing a positive electrode active material, a binder, a conductive agent, etc. As the binder, for example, fluororesins such as polytetrafluoroethylene, rubber particles, and acrylic resins can be listed. As the conductive agent, for example, conductive carbon materials can be listed. As the conductive carbon material, for example, natural graphite, artificial graphite, carbon black, and carbon fiber can be listed.
[0062] The positive electrode may further include a positive electrode current collector that holds the positive electrode mixture. Examples of the material of the positive electrode current collector include stainless steel, aluminum, and titanium.
[0063] In the case of a coin-shaped battery, a positive electrode current collector having an L-shaped cross section may be mounted on positive electrode mixture particles to form a positive electrode, or the positive electrode may be formed only by positive electrode mixture particles. The positive electrode mixture particles may be obtained by, for example, compressing and drying a wet positive electrode mixture prepared by adding an appropriate amount of water to a positive electrode active material.
[0064] In the case of a cylindrical battery, a positive electrode having a sheet-shaped positive electrode collector and a positive electrode held in a positive electrode mixture layer of the positive electrode collector can be used. As a sheet-shaped positive electrode collector, a porous collector is preferred. As a porous collector, porous metal mesh, mesh, punching metal, etc. can be listed. The positive electrode mixture layer can be obtained, for example, by applying the above-mentioned positive electrode mixture in a wet state to the surface of the sheet-shaped positive electrode collector or filling it in the positive electrode collector, pressing and drying in the thickness direction.
[0065] (negative electrode)
[0066] The negative electrode includes the above-mentioned lithium alloy. The lithium alloy is formed into any shape and thickness according to the shape, size, specification performance, etc. of the lithium primary battery. Since the lithium alloy includes Mg, Mg with relatively high strength remains at the end of discharge, so the negative electrode can be formed by using only a lithium alloy sheet (foil) instead of a current collector such as copper foil. In addition, in a lithium alloy containing both Al and Mg, since the Li in the negative electrode can be effectively used without reservation, the discharge capacity can be increased compared with the case of metallic lithium and a lithium alloy containing only Al and Mg.
[0067] In the case of a coin-shaped battery, a strip-shaped lithium alloy may be punched into a disc-shaped lithium alloy for use as a negative electrode. In the case of a cylindrical battery, a sheet-shaped lithium alloy may also be used as a negative electrode. The sheet is obtained, for example, by extrusion molding. More specifically, in a cylindrical battery, a lithium alloy foil having a shape in a length direction and a width direction is used.
[0068] (Non-aqueous electrolyte)
[0069] The nonaqueous electrolyte solution includes, for example, a nonaqueous solvent and a lithium salt. The concentration of lithium ions (total concentration of lithium salts) contained in the nonaqueous electrolyte solution is, for example, 0.2 mol / L to 2.0 mol / L, or 0.3 mol / L to 1.5 mol / L.
[0070] As the non-aqueous solvent, organic solvents that are generally used in non-aqueous electrolytes for lithium primary batteries can be cited. As the non-aqueous solvent, ethers, esters, carbonates, etc. can be cited. As the non-aqueous solvent, dimethyl ether, γ-butyrolactone, propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, 1,2-dimethoxyethane (DME), 1,2-diethoxyethane, methyl acetate, ethyl acetate, propyl acetate, etc. can be used. The non-aqueous electrolyte can contain one non-aqueous solvent or two or more non-aqueous solvents.
[0071] From the viewpoint of improving the discharge characteristics of lithium primary batteries, the nonaqueous solvent preferably includes a cyclic carbonate with a high boiling point and a chain ether with a low viscosity even at low temperatures. The cyclic carbonate preferably includes at least one selected from the group consisting of PC and EC, and PC is particularly preferred. The chain ether preferably includes DME.
[0072] Examples of lithium salts include lithium salts used as solutes in lithium primary batteries. Examples of such lithium salts include LiCF 3 SO 3 、LiClO 4 , LiBF 4 、LiPF 6 、LiRaSO 3 (Ra is a fluoroalkyl group having 1 to 4 carbon atoms), LiFSO 3 、LiN(SO 2 Rb)(SO 2 Rc) (Rb and Rc are each independently a fluoroalkyl group having 1 to 4 carbon atoms), LiN (FSO 2 ) 2 、LiN(SO 2 CF 3 ) 2 、LiN(SO 2 F)(POF 2 )、LiPO 2 F 2 、LiB(C 2 O 4 ) 2 , LiBF 2 (C 2 O 4 Among them, from the viewpoint of stability of lithium alloys containing Al and Mg, it is preferred to select LiCF 3 SO 3 , LiBF 4 and LiN(FSO 2 ) 2 The non-aqueous electrolyte may contain one type of these lithium salts, or may contain two or more types.
[0073] The non-aqueous electrolyte may further include other components other than the above-mentioned additives. As other components other than the above-mentioned additives, propane sultone, propylene sultone, ethylene sulfite, 3,2-dioxazole thiophene-2,2-dioxide, vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, adiponitrile, succinonitrile, succinic anhydride, etc. can be listed. Other components can be lithium salts, and can also generate lithium ions.
[0074] (Separator)
[0075] A lithium primary battery generally has a separator sandwiched between the positive electrode and the negative electrode. As the separator, a porous sheet formed of an insulating material resistant to the internal environment of the lithium primary battery can be used. Specifically, a nonwoven fabric made of a synthetic resin, a microporous membrane made of a synthetic resin, or a laminate thereof can be cited.
[0076] As the synthetic resin used in the nonwoven fabric, for example, polypropylene, polyphenylene sulfide, polybutylene terephthalate, etc. can be cited. As the synthetic resin used in the microporous membrane, for example, polyolefin resins such as polyethylene, polypropylene, and ethylene-propylene copolymer can be cited. The microporous membrane can also contain inorganic particles as needed.
[0077] The thickness of the separator is, for example, 5 μm or more and 100 μm or less.
[0078] The structure of the lithium primary battery is not particularly limited. The lithium primary battery may be a coin-shaped battery having a stacked electrode group composed of a disk-shaped positive electrode and a disk-shaped negative electrode stacked with a separator. It may also be a cylindrical battery having a wound electrode group composed of a strip-shaped positive electrode and a strip-shaped negative electrode wound in a spiral with a separator.
[0079] Figure 1 A front view showing a portion of a lithium primary battery of one embodiment of the present disclosure as a cross section is shown. In the lithium primary battery 10, an electrode group formed by winding a positive electrode 1 and a negative electrode 2 with a separator 3 interposed therebetween is housed in a battery case 9 together with a non-aqueous electrolyte (not shown). A sealing plate 8 is installed at the opening of the battery case 9. A positive electrode lead 4 connected to the collector 1a of the positive electrode 1 is connected to the sealing plate 8. The negative electrode lead 5 connected to the negative electrode 2 is connected to the battery case 9. In addition, an upper insulating plate 6 and a lower insulating plate 7 are respectively arranged at the upper and lower parts of the electrode group to prevent internal short circuits.
[0080] "appendix"
[0081] The following techniques are disclosed through the description of the above embodiments.
[0082] (Technology 1)
[0083] A lithium primary battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte.
[0084] The positive electrode comprises at least one selected from the group consisting of manganese dioxide and graphite fluoride,
[0085] The negative electrode comprises a lithium alloy.
[0086] The lithium alloy contains aluminum, magnesium, and at least one selected from the group consisting of sodium and calcium.
[0087] The total content of the aluminum and the magnesium in the lithium alloy is 0.02 mass % or more and 10 mass % or less,
[0088] The total content of the sodium and the calcium in the lithium alloy is 0.02 mass % or less.
[0089] (Technique 2)
[0090] The lithium primary battery according to technology 1, wherein the total content of the aluminum and the magnesium in the lithium alloy is 0.05 mass % or more and 8 mass % or less.
[0091] (Technique 3)
[0092] The lithium primary battery according to technology 1 or 2, wherein the total content of the sodium and the calcium in the lithium alloy is 0.001 mass % or more and 0.018 mass % or less.
[0093] (Technique 4)
[0094] The lithium primary battery according to any one of techniques 1 to 3, wherein the nonaqueous electrolyte solution contains at least one additive selected from the group consisting of cyclic imide compounds, phthalate compounds, and isocyanate compounds.
[0095] (Technique 5)
[0096] The lithium primary battery according to technology 4, wherein the cyclic imide compound includes at least one selected from the group consisting of phthalimide and N-substituted phthalimide.
[0097] (Technique 6)
[0098] The lithium primary battery according to technology 5, wherein the N-substituted phthalimide includes at least one selected from the group consisting of N-hydroxyphthalimide, N-(2-hydroxyethyl)phthalimide, N-(cyclohexylthio)phthalimide and N-(phenylthio)phthalimide.
[0099] (Technique 7)
[0100] The lithium primary battery according to any one of Aspects 4 to 6, wherein the content of the cyclic imide compound in the nonaqueous electrolyte is 1% by mass or less.
[0101] (Technology 8)
[0102] The lithium primary battery according to any one of techniques 4 to 7, wherein the phthalate ester compound includes a phthalate diester compound.
[0103] (Technique 9)
[0104] The lithium primary battery according to technology 8, wherein the phthalic acid diester compound includes dimethyl phthalate.
[0105] (Technology 10)
[0106] The lithium primary battery according to any one of Aspects 4 to 9, wherein the content of the phthalate compound in the nonaqueous electrolyte is 1% by mass or less.
[0107] (Technology 11)
[0108] The lithium primary battery according to any one of techniques 4 to 10, wherein the isocyanate compound includes a diisocyanate compound.
[0109] (Technology 12)
[0110] The lithium primary battery according to technology 11, wherein the diisocyanate compound includes at least one selected from the group consisting of hexamethylene diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, and isophorone diisocyanate.
[0111] (Technology 13)
[0112] The lithium primary battery according to any one of Aspects 4 to 12, wherein the content of the isocyanate compound in the nonaqueous electrolyte is 3% by mass or less.
[0113] [Example]
[0114] Hereinafter, the present disclosure will be specifically described based on Examples and Comparative Examples, but the present disclosure is not limited to the following Examples.
[0115] 《Examples 1 to 8, Comparative Examples 1 to 13》
[0116] (Production of positive electrode)
[0117] 5 parts by mass of Ketjen black as a conductive agent, 5 parts by mass of polytetrafluoroethylene as a binder, and an appropriate amount of pure water were added to 100 parts by mass of the positive electrode active material and kneaded to prepare a wet positive electrode mixture. Electrolytic manganese dioxide (MnO 2 ), graphite fluoride ((CF) n ) or iron disulfide (FeS 2 ).
[0118] Next, the positive electrode mixture is filled in a positive electrode current collector formed by a porous metal mesh with a thickness of 0.1 mm made of stainless steel (SUS444) to make a positive electrode precursor. Then, the positive electrode precursor is dried, rolled by roller pressing, and cut into a size of 3.5 cm in length and 20 cm in width, thereby obtaining a positive electrode. Next, a portion of the filled positive electrode mixture is peeled off, and one end of the positive electrode lead made of SUS444 is resistance welded to the portion where the positive electrode current collector is exposed.
[0119] (Production of negative electrode)
[0120] The lithium alloy foil (thickness 250 μm) was cut into a size of 3.7 cm in length and 22 cm in width to obtain a negative electrode. One end of a nickel negative electrode lead was connected to a specified position of the negative electrode by crimping. The lithium alloy foil used was a lithium alloy foil having Al, Mg, Na, and Ca contents as shown in Table 1. The content of Al, etc. in the lithium alloy was determined by ICP emission spectrometry or atomic absorption spectrometry, and the "-" in the column of the content of Al, etc. in the lithium alloy indicates that Al, etc. were not detected by ICP emission spectrometry or atomic absorption spectrometry.
[0121] (Production of Electrode Group)
[0122] The positive electrode and the negative electrode were wound with a separator interposed therebetween to produce an electrode group. A 25 μm-thick polypropylene microporous film was used as the separator.
[0123] (Preparation of non-aqueous electrolyte)
[0124] LiCF 3 SO 3 The non-aqueous electrolyte was prepared by dissolving it in a mixed solvent of PC, EC and DME (volume ratio 3:2:5) at a concentration of 0.5 mol / L.
[0125] (Assembly of lithium primary batteries)
[0126] The electrode group is housed in a cylindrical battery case that also serves as a negative terminal. The battery case uses an iron case (outer diameter 17 mm, height 45.5 mm). Next, after injecting a non-aqueous electrolyte into the battery case, the opening of the battery case is sealed with a metal sealing plate that also serves as a positive terminal. The other end of the positive lead is connected to the sealing plate, and the other end of the negative lead is connected to the inner bottom surface of the battery case. A lithium primary battery is made in this way. It should be noted that A1 to A8 in Table 1 are batteries of Examples 1 to 8. B1 to B13 are batteries of Comparative Examples 1 to 13.
[0127] The batteries of the examples and comparative examples thus obtained were aged for 3 days in an atmosphere at 45° C. after assembly, and the following evaluations were performed.
[0128] [evaluate]
[0129] (initial capacity)
[0130] The aged battery was discharged at a constant current of 2.5 mA in an environment of 20° C. until the battery voltage reached 0.9 V. The discharge time at this time was measured to determine the initial capacity.
[0131] (Capacity after saving)
[0132] The aged battery was stored at 85° C. for 3 months. The stored battery was discharged at a constant current of 2.5 mA at 20° C. until the battery voltage reached 0.9 V. The discharge time was measured to determine the post-storage capacity.
[0133] (Capacity degradation rate after storage)
[0134] Using the initial capacity and the capacity after storage obtained above, the capacity degradation rate after storage was obtained according to the following formula.
[0135] Capacity degradation rate after storage (%) = {1-(capacity after storage / initial capacity)}×100
[0136] The evaluation results are shown in Table 1. In addition, the initial capacity and the capacity after storage in Table 1 are expressed as relative values (indexes) when the initial capacity of the battery B1 of Comparative Example 1 is set to 100.
[0137] [Table 1]
[0138]
[0139] Compared with batteries B1 to B12, batteries A1 to A7 have larger initial and post-storage capacities, smaller capacity degradation rates, and reduced capacity reduction after high-temperature storage. Battery A8, in which graphite fluoride is used as the positive electrode active material, also has larger initial and post-storage capacities and smaller capacity degradation rates. Battery B13, in which iron disulfide is used as the positive electrode active material, has significantly reduced capacity after storage and significantly increased capacity degradation rates.
[0140] When comparing batteries A1 to A7 with battery B3, batteries A1 to A7 containing trace amounts of at least one of Na and Ca in the Li—Al—Mg alloy had larger initial and post-storage capacities and smaller capacity degradation rates than battery B3.
[0141] The capacity degradation rate of batteries A1 to A7 is 5.5% to 5.6%, and the capacity degradation rate of battery B3 is 7.5%. The improvement in the capacity degradation rate of batteries A1 to A7 relative to battery B3 is about 25% to about 27% (B3→A1 to A7). For example, the improvement in the capacity degradation rate of battery A1 relative to battery B3 is calculated by {(7.5-5.6) / 7.5}×100. It should be noted that in batteries A1 to A7 and battery B3, the positive electrode active material is manganese dioxide, and the Li alloy contains a total of 0.02 to 10% by mass of Al and Mg.
[0142] In the case where the Li alloy contains Al but not Mg, if trace amounts of Na and Ca are contained in the Li alloy, the initial and post-storage capacities become smaller, and the capacity degradation rate of battery B9 relative to battery B1 is not improved (B1: capacity degradation rate 10.0% → B9: capacity degradation rate 10.1%).
[0143] In the case where the Li alloy contains Al and does not contain Mg, if trace amounts of Na and Ca are contained in the Li alloy, the initial capacity decreases, and the improvement in the capacity degradation rate of battery B10 relative to battery B2 is as small as about 8% (B2: capacity degradation rate 11.1% → B10: capacity degradation rate 10.2%).
[0144] When the Li alloy does not contain Al and Mg, if a trace amount of Na and Ca is contained in the Li alloy, the initial and post-storage capacities become smaller, and the improvement in the capacity degradation rate of battery B8 relative to battery B7 is as small as about 12% (B7: capacity degradation rate 24.7% → B8: capacity degradation rate 21.8%).
[0145] When the total content of Al and Mg in the Li alloy is greater than 10 mass % and / or the total content of Na and Ca in the Li alloy is greater than 0.02 mass %, the initial and post-storage capacities decrease and the capacity degradation rate increases (B4, B11, B12).
[0146] From the above results, it can be seen that when the lithium alloy contains Al and Mg in a total range of more than 0.02 mass % and less than 10 mass %, by including trace amounts of at least one of Na and Ca in the lithium alloy, a battery with large initial and after storage capacity and a small capacity degradation rate can be obtained.
[0147] 《Examples 9 to 17》
[0148] In the preparation of the negative electrode, the lithium alloy foil used has the contents of Al, Mg, Na and Ca as shown in Table 2. In the preparation of the non-aqueous electrolyte, additives are further included in the non-aqueous electrolyte as needed. The additives use the compounds shown in Table 2. The content (mass %) of the additives in the non-aqueous electrolyte is the value shown in Table 2.
[0149] Batteries A9 to A17 of Examples 9 to 17 were prepared in the same manner as the battery A1 of Example 1 except for the above, and were evaluated.
[0150] The evaluation results are shown in Table 2. In Table 2, the initial capacity and the capacity after storage are expressed as relative values (indexes) with the initial capacity of the battery B1 of Comparative Example 1 being 100.
[0151] [Table 2]
[0152]
[0153] Batteries A9 to A17 had large initial capacities and capacities after storage, and their capacity degradation rates were all reduced. Batteries A10 to A17 containing additives in the non-aqueous electrolyte had a further reduced capacity degradation rate.
[0154] Industrial Applicability
[0155] The lithium primary battery of the present disclosure can be suitably used as a main power source or a memory power source of various meters (for example, smart meters for electricity, water, gas, etc.), for example.
[0156] The present invention has been described with respect to the presently preferred embodiments, but such disclosure is not to be construed in a limiting sense. Various modifications and changes should be apparent to those skilled in the art in the art of the present invention upon reading the above disclosure. Therefore, the appended claims should be construed as including all modifications and changes without departing from the spirit and scope of the present invention.
[0157] Description of Reference Numerals
[0158] 1: Positive electrode, 1a: Positive electrode current collector, 2: Negative electrode, 3: Separator, 4: Positive electrode lead, 5: Negative electrode lead, 6: Upper insulating plate, 7: Lower insulating plate, 8: Sealing plate, 9: Battery case, 10: Lithium primary battery
Claims
1. A lithium primary battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, The positive electrode comprises at least one selected from the group consisting of manganese dioxide and graphite fluoride, The negative electrode comprises a lithium alloy, The lithium alloy contains aluminum, magnesium, and at least one selected from the group consisting of sodium and calcium, The total content of the aluminum and the magnesium in the lithium alloy is 0.02 mass % or more and 10 mass % or less, The total content of the sodium and the calcium in the lithium alloy is 0.02 mass % or less.
2. The lithium primary battery according to claim 1, wherein: The total content of the aluminum and the magnesium in the lithium alloy is 0.05 mass % or more and 8 mass % or less.
3. The lithium primary battery according to claim 1, wherein: The total content of the sodium and the calcium in the lithium alloy is 0.001 mass % or more and 0.018 mass % or less.
4. The lithium primary battery according to claim 1, wherein: The non-aqueous electrolyte solution includes at least one additive selected from the group consisting of cyclic imide compounds, phthalate compounds, and isocyanate compounds.
5. The lithium primary battery according to claim 4, wherein: The cyclic imide compound includes at least one selected from the group consisting of phthalimide and N-substituted phthalimide.
6. The lithium primary battery according to claim 5, wherein: The N-substituted phthalimide includes at least one selected from the group consisting of N-hydroxyphthalimide, N-(2-hydroxyethyl)phthalimide, N-(cyclohexylthio)phthalimide, and N-(phenylthio)phthalimide.
7. The lithium primary battery according to claim 4, wherein: The content of the cyclic imide compound in the non-aqueous electrolyte is 1 mass % or less.
8. The lithium primary battery according to claim 4, wherein: The phthalate compound includes a phthalic acid diester compound.
9. The lithium primary battery according to claim 8, wherein: The phthalic acid diester compound includes dimethyl phthalate.
10. The lithium primary battery according to claim 4, wherein: The content of the phthalate compound in the non-aqueous electrolyte is 1 mass % or less.
11. The lithium primary battery according to claim 4, wherein: The isocyanate compound includes a diisocyanate compound.
12. The lithium primary battery according to claim 11, wherein: The diisocyanate compound includes at least one selected from the group consisting of hexamethylene diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, and isophorone diisocyanate.
13. The lithium primary battery according to claim 4, wherein: The content of the isocyanate compound in the non-aqueous electrolyte is 3% by mass or less.
Citation Information
Patent Citations
Improved lithium cathode
JP1983209862A
Non-aqueous electrochemical cell with improved energy density
JP2005529467A
Lithium primary battery
WO2012066709A1